Penerapan Metode Drama “Study Group” untuk Meningkatkan Motivasi dan Pemahaman PAI di MAN 2 Lombok Tengah: Implementation of the "Study Group" Drama Method to Increase Motivation and Understanding of Islamic Education at MAN 2 Central Lombok - Restu Holid Imawan; Nurul Imtihan; Muhammad Ghazali; Muhammad Muhammad (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
This study aims to determine the effect of implementing the "study group" drama method on students' motivation to learn and understanding of Islamic Religious Education (PAI) concepts at MAN 2 Central Lombok. The background of this study is the low motivation to learn and students' understanding of concepts, due to the dominance of conventional, teacher-centered learning methods. Therefore, more active, interactive, and meaningful learning innovations are needed. This study uses a quantitative, quasi-experimental approach with a Non-Equivalent Control Group Design. The research sample consists of two classes: class XI MIA 2, the experimental class that received the "study group" drama method treatment, and class XI IKG, the control class that used conventional learning methods. Data collection techniques included learning motivation questionnaires, PAI concept-understanding tests, and observation sheets. Data analysis used descriptive tests and inferential tests, including paired-sample and independent-sample t-tests. The results showed a significant increase in students' motivation to learn and understanding of PAI concepts in the experimental class compared to the control class. The average increase in learning motivation for the experimental class was 17.15 points, while for the control class it was 5.45 points.Meanwhile, the increase in understanding of Islamic Religious Education concepts in the experimental class was 19.40 points, 8.70 points higher than that of the control class. The results of the statistical test showed a p-value of 0.000 (<0.05), indicating that H? is rejected and H? is accepted. Thus, it can be concluded that the application of the "study group" drama method has a significant effect in increasing students' motivation to learn and understanding of Islamic Religious Education concepts. This method has been proven more effective than conventional learning because it fosters an active, collaborative, and enjoyable learning environment.